Gender Equality Education for Women in the Modern Era from the Perspective of the Qur'an - Nazha Virani Shopian; Tulus Musthafa (Penerbit Hellow Pustaka, 2026)
This study aims to examine gender equality in education for women in the modern era from the perspective of the Qur'an. Amidst the advancement of the times and growing awareness of the importance of equal access to education, women now have greater opportunities to participate in the field of education. However, reality shows that challenges still persist, especially in areas that strongly uphold patriarchal norms. In Islam, the Qur'an places great emphasis on the importance of education without discriminating based on gender. Using a qualitative method and a library research approach, this study analyzes Qur'anic verses that emphasize the principles of justice, equality, and human dignity in the pursuit of knowledge. The findings indicate that the Qur'an fully supports education for women and regards it as a fundamental human right. Gender equality in education, as reflected in Qur'anic teachings, is relevant to the current condition of women who are increasingly active in education and development. Therefore, integrating Qur'anic values into the modern education system is essential to realize a just, inclusive, and progressive society.